2017
DOI: 10.1007/s12149-017-1213-0
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive and prognostic value of 18F-DOPA PET/CT in patients affected by recurrent medullary carcinoma of the thyroid

Abstract: F-DOPA PET/CT scan has an important prognostic value in predicting disease progression and mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 21 publications
2
37
2
2
Order By: Relevance
“…In our institution, 18 F-DOPA-PET/CT is performed for whole-body tumour staging in MTC since numerous studies demonstrated superiority to 18 F-FDG hybrid imaging [6, 810, 35]. The detection of liver metastases in MTC patients, however, is difficult due to the typically small size with correspondingly low 18 F-DOPA uptake or size below the spatial resolution of PET imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, 18 F-DOPA-PET/CT is performed for whole-body tumour staging in MTC since numerous studies demonstrated superiority to 18 F-FDG hybrid imaging [6, 810, 35]. The detection of liver metastases in MTC patients, however, is difficult due to the typically small size with correspondingly low 18 F-DOPA uptake or size below the spatial resolution of PET imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its greater spatial resolution, lower radiation dose and improved diagnostic accuracy as well as patients convenience, 68 Gallium-SSTR-PET has replaced SSTR scintigraphy as the standard imaging technique for NEN staging [8•].…”
Section: Gallium-sstr Imagingmentioning
confidence: 99%
“…Using the chelator DOTA (tetra-zacyclododecane-tetraacetic acid), the radiometal 68 Gallium (Ga) is conjugated with an SSA peptide. While 68 Ga-DOTATOC and -NOC use octreotide (Tyr-3/1-Nal3) with affinity for the SSTR subtypes 2, 3, and 5, 68 Ga -DOTATATE uses octreotate which has an enhanced affinity for the SSTR subtype 2 [36]. Clinically, there is no real difference between 68 Ga-DOTATOCand 68 Ga-DOTATATE-based PET imaging [37,38], their respective use often depends on the availability of the centers.…”
Section: Gallium-sstr Imagingmentioning
confidence: 99%
See 2 more Smart Citations